FACTORS INFLUENCING PRE-SERVICE TEACHERS' SELF-CONFIDENCE IN TEACHING DURING THE COVID-19 PANDEMIC (Malaysian Journal of Learning and Instruction, 2023)
Purpose – Pre-service teachers, who are practising teachers are exposed to numerous technical skills at university. Studies on theuse of technology on pre-service teachers’ self-confidence are still in their infancy, despite the abundance of studies addressing pre-service teachers’ intention to utilise technology in online learning. Therefore, this study seeks to investigate pre-service teachers’ use of technology and their confidence in handling online classes effectively.Methodology – A survey was conducted on 93 teachers at two randomly selected universities in Malaysia during the early stages of the COVID-19 pandemic (March-May 2020) through online data collection. A five-point Likert scale-adapted questionnaire on preservice teachers’ perceptions of technology use, effort, and confidence was administered to the respondents. The questionnaire was validated by three experts and data were analysed empirically using structural equation modelling-partial least-squares analysis.Findings – According to the study’s findings, pre-service teachers held that technology was a great tool for online instruction and thatpeer contact helped them broaden their understanding about teaching. Despite this, there was no significant correlation between the use of technology and pre-service teachers’ self-confidence. Nevertheless, the effort factor was found to mediate between pre-service teachers’ confidence and technology.Significance – The results of this study provide important findings; that pre-service teachers could train their minds to put forth specific effort, such as increasing their interpersonal experience to support and enhance their online teaching. This in turn could help pre-service teachers in preparing to embark on technology-related activities to enable them to work with students more frequently and to support and enhance online education.